Minimal Clinically Important Difference of Grip and Pinch Strength in Women With Thumb Carpometacarpal Osteoarthritis When Compared to Healthy Subjects - Villafañe, Jorge Hugo; Valdes, Kristin; Bertozzi, Lucia; Negrini, Stefano (Rehabilitation nursing, 2017)
The primary objective of this study was to compare grip and pinch strength between women with carpometacarpal (CMC) osteoarthritis (OA) between affected and unaffected sides of the body in patients or dominant and nondominant sides in healthy subjects. The secondary aim was to establish the cutoff value scores for the minimal clinically important difference (MCID) for grip strength, tip, and tripod pinch. A prospective case-control study. One hundred ten women participated in the study. The CMC OA group consisted of 57 patients, and the control group consisted of 53 healthy subjects. Grip strength, tip, and tripod pinch were assessed bilaterally. The two-way analysis of variance (ANOVA) was conducted to determine the differences between sides of the body and between the groups. The post hoc analysis indicated that the patients in the CMC OA group indicated statistically significant lower scores on the grip and pinch strength (all, p < .001). The MCID from baseline score in this patient population was 0.84 kg for grip, 0.33 kg for tip, and 0.35 kg for tripod pinch for the affected right arm and 1.12 kg for grip, 0.23 kg for tip, and 0.30 kg for tripod pinch for the unaffected left side. Women with CMC OA have significantly decreased grip strength, tip, and tripod pinch as compared to their healthy counterparts and may experience functional consequences because of this limitation. Our study established the MCID for grip and pinch strength for individuals with CMC OA and their healthy counterparts.